Heart Rate An Emerging Cardiovascular Risk Factor (University Heart Journal, 2012)
The development of cardiovascular disease (CVD) is usually caused by multiple risk factors, which interact to produce an individuals total CVD risk. Therefore the guidelines on the prevention of CVD recommend the preventive measures be based on individuals levels of total CVD risk so that the most intensive risk factor management can be directed towards those at highest risk. Elevated resting heart rate is a known independent   cardiovascular risk factor but is not included in any risk estimating system-Coronary risk chart or SCORE(Systematic Coronary Risk Evaluation).which are used for estimation of individuals 10 year risk of a CVD event based on gender, age, total cholesterol, smoking status and systolic blood pressure. The findings several epidemiological studies showed an association between elevated heart rate an increased risk of allcause mortality and morbidity in general population, hypertensives, diabetics and those with CAD. DOI: http://dx.doi.org/10.3329/uhj.v8i1.11665 University Heart Journal Vol. 8, No. 1, January 2012